Enhanced performance of Zn and Co co-doped MoO3 nanosheets as gas sensor for n-butylamine. Issue 22 (15th November 2022) - Liu, Aiai; Liu, Tao; Fu, Haitao; Yin, Xitao; Liu, Ke; Yu, Jingkun
Abstract: High operating temperature of metal oxide sensor devices hinders their practical applications. In order to reduce operating temperature, molybdenum trioxide (MoO3 ) nanosheets co-doped with zinc (Zn) and cobalt (Co) were successfully prepared by simple one-step hydrothermal method and characterized by X-ray diffraction, scanning electron microscopy, and X-ray photoelectron spectroscopy, and by using WS-30A gas sensor measurement system. The sensor exhibited high response to n -butylamine gas at low temperature. In particular, the response of Zn and Co co-doped MoO3 sensor was higher than that of pure MoO3 and retained excellent selectivity of MoO3 to n -butylamine. Optimum operating temperature gradually decreased with increasing Co and Zn doping amount. Multi-doping system shows great potential for the development and application of sensors, and provides feasible method for reducing their operating temperature of the sensor.